Acceptability and design of video-based research on healthcare communication: evidence and recommendations - Parry, Ruth; Pino, Marco; Faull, Christina; Feathers, Luke (Elsevier, 2016)
Objectives: To contribute to understandings about acceptability and risks entailed in video-based research on healthcare communication. To generate recommendations for non-covert video-based research on healthcare communication − with a focus on maximising its acceptability to participants, and managing and reducing its risks. Methods: A literature review and synthesis of (a) empirical research on participant acceptability and risks of video recording; (b) regulations of professional and governmental bodies; (c) reviews and commentaries; (d) guidance and recommendations. These were gathered across several academic and professional fields (including medical, educational, and social scientific). Results: 36 publications were included in the review and synthesis (7 regulatory documents, 7 empirical, 4 reviews/commentaries, 18 guidance/recommendations). In the context of research aiming in some way to improve healthcare communication: •Most people regard video-based research as acceptable and worthwhile, whilst also carrying risks. •Concerns that recording could be detrimental to healthcare delivery are not confirmed by existing evidence. •Numerous procedures to enhance acceptability and feasibility have been documented, and our recommendations collate these. Conclusion and practice implications: The recommendations are designed to support deliberations and decisions about individual studies and to support ethical scrutiny of proposed research studies. Whilst preliminary, it is nevertheless the most comprehensive and detailed currently available.